Transgenerational plasticity and environmental stress: do paternal effects act as a conduit or a buffer?. (12th December 2015) - Guillaume, Annie S.; Monro, Keyne; Marshall, Dustin J.
Summary: For most organisms, early life‐history stages are the most sensitive to environmental stress and so transgenerational phenotypic plasticity, whereby the parental environment and offspring environment interact to alter the phenotype of the offspring, is viewed as key to promoting persistence in the face of environmental change. While there has been long‐standing interest in the role of transgenerational plasticity via the maternal line (traditionally the field of maternal effects), increasingly it appears that paternal effects can also play a role. Despite the emerging role of paternal effects in studies of global change, key knowledge gaps remain: first, whether paternal effects act to increase or decrease offspring performance remains largely unexplored; second, the relative roles of maternal and paternal effects are rarely disentangled; and third, the role of environmental variation, a key determinant of the benefits of transgenerational plasticity, has not been explored with regard to paternal effects. Here, we explore all three issues using the marine tubeworm Galeolaria caespitosa, an important habitat‐forming species in southern Australia. We found that both paternal and maternal experiences affected key stages of offspring performance (fertilization and larval development) and, surprisingly, paternal effects were often stronger than maternal effects. Furthermore, we found that paternal effects often reduced offspring performance, especially when environments varied compared with when environments were stable. Our results suggest that, while transgenerational plasticity may play an important role in modifying the impacts of global change, these effects are not uniformly positive. Importantly, paternal effects can be as strong, or stronger, than maternal effects and environmental variability strongly alters the impacts of paternal effects. Abstract : Lay Summary